De novo assembly and characterization of leaf transcriptome for the development of EST-SSR markers of the non-model species Indigofera szechuensis. (October 2016) - Guo, Li-Na; Zhao, Xue-Li; Gao, Xin-Fen
Abstract: Indigofera szechuensis Craib, a species endemic to Hengduan Mountains in China, is widely distributed across a range of habitats, including slopes, trailsides, and riverbanks. This species serves as a good model to examine flexible adaptation of plants. In this study, we reported the transcriptome sequence of this species and developed a set of SSR markers for such evolutionary studies. Approximately 19.4 million clean reads from the leaves of I . szechuensis were generated through transcriptome sequencing, and 43, 896 unigenes with an average length of 798.54 bp were obtained. A total of 27, 320 (62.2%) unigenes were annotated for their functions, and 17, 422 and 8017 unigenes could be aligned to the GO and COG database, respectively. By searching against the Kyoto Encyclopedia of Genes and Genomes Pathway database (KEGG), 5682 unigenes were assigned to 118 KEGG pathways that belong to five main categories, i.e ., organismal systems, cellular processes, environmental information processing, metabolism, and genetic information processing. We further identified 4052 potential SSR sites. Using 102 randomly selected EST-SSRs, 73 markers were successfully amplified with the expected size in I . szechuensis and 67-71 markers of these 73 SSRs in eight other Indigofera species. We firstly established a public trascriptome platform for the species-rich genus Indigofera . The SSR sites identified here provide additional resources for development of molecular markers for further evolutionary studies for this species and congeners. Highlights: High-throughput sequencing of Indigofera szechuensis using Illumina HiSeqTM 2500. 73EST-SSR primers were successfully developed for I . szechuensis . The transferability of EST-SSR markers to eight other closely related species was examined.